Inclusão de alunos com deficiência múltipla : análise de um programa de apoio - Aráoz, Susana Maria Mana de (2009)
The aim of this research was to analyze the effectiveness of the implementation of a Program of Support for Inclusion of Multi Disabled Students using techniques such as MAP and PATH as facilitators. The techniques disclosed by Pearpoint, Forest and O'Brien proposed a work centered on the person and acting with a positive vision of the future developed by groups where families, professionals and community members participate. The participants were four students between 7 and 14 years of a specialized institution that is in the city, the one that serves more students with multiple disabilities, and they began to be a part of the category of "participating beneficiaries." Worked in groups four facilitators participants 1', family members; four "facilitators participants 2", professionals of the specialized institution; and four facilitators participants 3 , members of the general community. It was proposed and carried out three meetings to develop the technique MAP for the removal of the needs and characteristics of each "participating beneficiary", to outline a plan of action. There was full involvement of participants. Six meetings were proposed with the PATH technique for monitoring the actions and made six in a group, five in another because the difficulty of one of the members and four in two other groups because of problems of prohibition of accessing roads. Requirements were raised to improve the educational programs to encourage the development of communication, activities of daily life, inclusion in regular schools, inclusion in the general community, the need for diagnosis, family support and effective relationship between education and health areas. The actions performed successfully forward improvements in care of the specialized institution, getting advice online first and then, presence advice with a three-day seminar for parents and teachers, all subsidized by national and international institutions. It was started a work on monitoring activities of daily living at home and social inclusion in areas of "participating beneficiaries" focusing mainly the churches that are available. The diagnoses were scheduled in a philanthropic hospital care and that provides a predictable treatment and it was got aids of volunteers so that families could travel to the state capital for these services. Three of the "beneficiaries participants" sought the regular education system, where only one has registered but he could not attend for lack of educational help. It was initiated in this case, a work in partnership between management, teachers and the school's specialized institution, volunteers and the researcher to achieve the inclusion. It can be concluded that the techniques MAP and PATH facilitated the actions to improve the family, social and educational inclusion because they followed the plan. It is desirable that the groups would have a greater number of members and that facilitators of the community could join to the centered group on the person and also to a group of volunteers to maximize the overall effectiveness of actions. Also, the partnership achieved through the regular school, in a case could be extended to all, encouraging the exchange of shares between the regular education, special education and health services.